2018
DOI: 10.1002/ags3.12210
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of a perioperative bacteriological culture to treat patients with postoperative pneumonia after esophagectomy

Abstract: AimThe aim of the present study was to examine the usefulness of a perioperative bacteriological culture in predicting the pathogenic bacteria responsible for postoperative pneumonia after esophagectomy.MethodsThis study included 293 consecutive esophageal cancer patients who underwent esophagectomy with gastric conduit reconstruction. We compared the pathological bacteria that were detected in bacteriological cultures of sputum, mouthwash and gastric fluid on the second postoperative day with the pathogenic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Because P.aeruginosa affected immunosuppressed patients, careful management would be essential for CD patients under treatment. 31 , 32 The current findings suggest that organisms at the site of SSI were resistant to the prophylactic antibiotic cefmetazole and that most of the antibiotic sensitivity results were the same between drainage fluid and of SSI bacterial culture. This suggested that sensitivity results in drainage fluid could guide the choice of an antibiotic.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Because P.aeruginosa affected immunosuppressed patients, careful management would be essential for CD patients under treatment. 31 , 32 The current findings suggest that organisms at the site of SSI were resistant to the prophylactic antibiotic cefmetazole and that most of the antibiotic sensitivity results were the same between drainage fluid and of SSI bacterial culture. This suggested that sensitivity results in drainage fluid could guide the choice of an antibiotic.…”
Section: Discussionmentioning
confidence: 60%
“…Our data also showed that E. faecalis and P. aeruginosa were significantly detected in CD patients with organ/space SSI. Because P.aeruginosa affected immunosuppressed patients, careful management would be essential for CD patients under treatment 31,32 . The current findings suggest that organisms at the site of SSI were resistant to the prophylactic antibiotic cefmetazole and that most of the antibiotic sensitivity results were the same between drainage fluid and of SSI bacterial culture.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies report conflicting results about the relationship between the presence of pathogenic bacteria detected in perioperative routine cultures and postoperative pneumonia 8,14,16) 8,14) . On the other hand, Matsui et al showed that detection of bacterial species by sputum culture on the first postoperative day was an independent risk factor of postoperative pneumonia 17) , although, this study did not focus on severity of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally considered that aspiration of oropharyngeal pathogens is one of the main causes of postoperative pneumonia 8,9) . Several studies identified pathogens in the oral cavity, dental plaque, and tracheal sputum as risk factors for respiratory infections after esophagectomy 10,11) .…”
Section: Introductionmentioning
confidence: 99%